Obstetric cholestasis: Outcome with active management. Issue 5 (17th March 2013) - Jain, Reenu; Suri, Vanita; Chopra, Seema; Chawla, Yogesh K.; Kohli, Krishan Kumar
Abstract Aim To study the nature and clinical outcome of pregnancies with obstetric cholestasis on active management and to correlate perinatal outcome to gestational age at delivery. Material and Methods This prospective randomized study included 69 women with obstetric cholestasis. Fetal surveillance began at 34 weeks or later at diagnosis and included daily maternal record of fetal movements, and biophysical profile (i.e. non stress test, the four quadrant amniotic fluid index). Fetal monitoring was conducted weekly before 36 weeks and biweekly after that. Randomization into two groups was done where one group was planned for delivery at 37 weeks whereas in the other group, pregnancy was carried to 38 weeks under surveillance. The primary outcome variable was correlation of fetal and neonatal complication rates to gestational age at delivery. Results There were no stillbirths in the study. No episode of fetal asphyxia or bradycardia was observed. The overall rate of meconium passage was 7.46% (5/67). However, there was no case of meconium aspiration syndrome. Women delivering at or after 38 weeks had a lower incidence of cesarean section (17.85% vs 25.8%), neonatal nursery admission (17.85% vs 22.5%), and neonatal jaundice (17.85% vs 19.35%) compared to those delivering at 37 weeks. The differences between the two groups were, however, not found to be statistically significant. Conclusion The current study demonstrates that with active intervention, pregnancies with obstetric cholestasis can be carried to a later gestation under surveillance.